U-shaped metallic-yielding damper in building structures: Seismic behavior and comparison with a friction damper. (August 2015) - Bagheri, Saman; Barghian, Majid; Saieri, Farhad; Farzinfar, Ali
Abstract: This paper presents the performance of U-shaped metallic-yielding dampers in steel building frames as well as a comparison with rotational friction dampers, known as Friction Damper Devices (FDD). For this purpose, an installation detail to use a U-shaped damper in steel building frames was suggested. Next, each type of dampers was added to the 3, 5 and 10-story building frame models together with inverted V-braces. Nonlinear time history analyses were applied to models under four different earthquake ground motions. The results show that by adding dampers in both systems to moment resisting frames, nonlinear behavior is transferred from frame members to the damper system; therefore, structural damages are reduced or removed. According to the numerical results, adding the dampers decreases maximum base shear of the structure and the roof lateral displacements by cutting down about 6% to 40% and 13% to 57% using the U-shaped damper and about 15% to 41% and 9% to 53% using the FDD, respectively. Therefore, it can be said that the performance of the FDD in reducing maximum base shear of frames is slightly better than the U-shaped damper while the results are vice versa for frames lateral displacements.